Physiotherapy Interventions in Lateral Epicondylitis - Putra, Kadek Ari Widyakusuma; Kamayoga, I Dewa Gede Alit (PT. Kesehatan Gerak Fungsi Tubuh, 2022)
Background: Lateral epicondylitis, commonly called “tennis elbow”, is an overuse injury to the wrist extensor that causes inflammation resulting in degenerative changes such as tendinosis and micro-teared (small tears) in the fibrous tissue. The risk of lateral epicondylitis is highest in workers who lift heavy weights and workers whose work requires repetitive movements of the wrist extensors. Degenerative factors are also one of the factors that can affect the development of lateral epicondylitis. From Magnetic Resonance Imaging (MRI) scans of 369 patients without clinical complaints of lateral epicondylitis, MRI signs consistent with lateral epicondylitis were seen in 5.7% of individuals in the 18-30 years age group and 16% in individuals over 70 years of age. Objective: The purpose of this study is to summarize secondary data related to interventions that can be applied to cases of lateral epicondylitis. Methods: The study method used is a literature study using secondary data in journals related to physiotherapy management in cases of lateral epicondylitis obtained through Google Scholar, Science Direct, and PubMed. Results: Several studies have shown various interventions can be applied to overcome the problems experienced by patients with lateral epicondylitis and provide good results in overcoming pain and gripping muscle weakness. Conclusion: Several interventions can be given to overcome the problems experienced by lateral epicondylitis patients, such as Cyriax, low-level laser therapy, mulligan mobilization with movement, ultrasound, eccentric exercise, concentric exercise, and kinesiotaping. Based on the literature review results, it can be concluded that these interventions can have a good effect in overcoming complaints experienced by patients with lateral epicondylitis.